2018
DOI: 10.1371/journal.pone.0192452
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative genomic analysis of the multispecies probiotic-marketed product VSL#3

Abstract: Several probiotic-marketed formulations available for the consumers contain live lactic acid bacteria and/or bifidobacteria. The multispecies product commercialized as VSL#3 has been used for treating various gastro-intestinal disorders. However, like many other products, the bacterial strains present in VSL#3 have only been characterized to a limited extent and their efficacy as well as their predicted mode of action remain unclear, preventing further applications or comparative studies. In this work, the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 94 publications
4
38
0
Order By: Relevance
“…Using this sequence coverage, a strain with a load of one billion of CFU up to an overall load of 450 billions of CFU (declared in the product label), and therefore representing approximately 0.22% of the blend, should be theoretically covered by approximately 13 333 reads. The results obtained showed that 99.8% of the total reads matched with an identity of > 99% to the genomes of the 8 strains that had been previously described (Douillard et al, 2018). This confirmed the identity of the strains in this commercial VSL#3 product.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…Using this sequence coverage, a strain with a load of one billion of CFU up to an overall load of 450 billions of CFU (declared in the product label), and therefore representing approximately 0.22% of the blend, should be theoretically covered by approximately 13 333 reads. The results obtained showed that 99.8% of the total reads matched with an identity of > 99% to the genomes of the 8 strains that had been previously described (Douillard et al, 2018). This confirmed the identity of the strains in this commercial VSL#3 product.…”
Section: Resultssupporting
confidence: 79%
“…E). Since the urease activity was unique for S. thermophilus (Douillard et al , ) as confirmed by the metagenomic analysis that also showed S. thermophilus to have over 50 % abundance, we conclude that S. thermophilus in the VSL#3 blend is responsible for the urease activity.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations